Análise da função legislativa de 2015 a 2017: uma aplicação nos municípios cearenses - Viana Júnior, Azarias Gurgel (2020)
This paper aims to analyze the expenditure of the legislative function of the municipalities of Ceará. The methodology used in the data evaluation makes use of the panel data method. A database was built with information provided by Finbra, Firjan, IBGE, Rais, Siconfi and the comparabrasil site, covering a period from 2015 to 2017. To assess the relationship between control variables and their impact on spending on the legislative function , data referring to the twelfth, investment, urbanism function, municipal GDP per capita, education index, fiscal management index - FIRJAN, health index and employment dummy were used, which involve budgetary, financial and socioeconomic aspects. The results obtained show that an increase in the allocation of resources in investments produces a decrease in spending on the legislative function. Among other results obtained, there is a statistically significant relationship between the variables urbanism function and education index in the legislative function.